O Método MPT: desenvolvimento de ferramenta de gestão para empreendedores tecnológicos - Silva, Mônica Patrícia de França (2023)
The general objective of the study was to develop a management tool that is quick to understand for technological entrepreneurs. The methodology employed is based on the bibliographical study that took place from publications in university journals and repositories, and, in continuity, there was an application of an online questionnaire with specialists, members of a research group at the Federal University of Rio Grande do Norte (UFRN). The research was submitted and approved by the Research Ethics Committee (CEP) of the University Hospital Onofre Lopes. The management tool was developed by the researcher based on studies carried out in the literature and in practical experience. The tool was called the MTP Method (Matrix, Potential and Time). The experts' survey provided suggestions for the tool's presentation booklet, namely, an intuitive and uncomplicated textual language, enabling easy understanding of the content. The product generated was the booklet called “The MPT Method as a management tool”. Finally, the study concludes that it is possible to reach technological entrepreneurs through a simple and visual language.